Reviews: Charmaine Nelson, Slavery, Geography and Empire in Nineteenth-Century Marine Landscapes of Montreal and Jamaica, Routledge, London, 2016, 416 pages, hardback, ISBN 9781409468912, £110.00. ( 2018) - Birkeli, Helene Engnes
No abstract available